74.7k views
4 votes
-79 = 7w + 3(4w-1) Show all work

User Deathlock
by
5.9k points

2 Answers

6 votes

Answer:

w = -4

Explanation:

distribute the 3 in 3(4w-1), you should get 12w-3 and your full equation should be -79=7w+12w-3

add 3 to both side of the equation and you should get -76 = 7w+12w

add like terms and you should get -76 = 19w

divide 19 from both sides and you should get -4 = w

User Amokrane Chentir
by
6.0k points
6 votes

Answer:

w = -4

Explanation:

-79 = 7w + 3(4w-1)

Distribute

-79 = 7w +12w -3

Combine like terms

-79 = 19w -3

Add 3 to each side

-76 = 19w

Divide by 19

-76/19 = w

-4 = w

User Conor Livingston
by
5.7k points